Indigenous education : language, culture and identity - Jacob, W. James; Cheng, Sheng Yao; Porter, Maureen K. (Springer, 2015)
Indigenous Education is a compilation of conceptual chapters and national case studies that includes empirical research based on a series of data collection methods. The book provides up-to-date scholarly research on global trends on three issues of paramount importance with Indigenous education?language, culture, and identity. It also offers a strategic comparative and international education policy statement on recent shifts in Indigenous education, and new approaches to explore, develop, and improve comparative education and policy research globally. Contributing authors examine several social justice issues related to Indigenous education. In addition to case perspectives from 12 countries and global regions, the volume includes five conceptual chapters on topics that influence Indigenous education, including policy debates, the media, the united nations, formal and informal education systems, and higher education.